Hadrosaurian dinosaurs from the Maastrichtian Javelina Formation, Big Bend National Park, Texas. (16th June 2016) - Lehman, Thomas M.; Wick, Steven L.; Wagner, Jonathan R.
Abstract: Rare remains of hadrosaurian dinosaurs previously reported from the Maastrichtian Javelina Formation of West Texas had been attributed tentatively to either Edmontosaurus or Kritosaurus . Three recently recovered specimens include substantial skull parts and postcranial skeletal elements sufficient to recognize three distinct hadrosaurs. Two species are found in the lower part of the Javelina Formation; one of these is identified as Kritosaurus sp., confirming the earlier referral of specimens to this taxon. The most complete of these specimens combines features thought to be diagnostic of both K . navajovius Brown, 1910 and ' Naashoibitosaurus ' ostromi Hunt and Lucas, 1993 and exhibits some unique attributes such that its specific identity remains uncertain. A second species, documented by a single specimen found near the base of the Javelina Formation, is inadequate to confidently identify but appears to represent a 'solid-crested' saurolophine with frontals having upturned processes along the midline, similar to those that brace the posterior side of the narial crest in Saurolophus . A third hadrosaur is represented at a bonebed in the uppermost part of the Javelina Formation. Its remains are sufficient to justify designation as a new species ?Gryposaurus alsatei . The skull roof elements are similar to those in species of Gryposaurus, and although no parts of the narial crest are preserved, the bordering elements indicate that ?G. alsatei was a 'flat-headed' saurolophine. Referral of ?G. alsatei to Gryposaurus would constitute a significant temporal range extension for the genus into late Maastrichtian time, and if correct, this long-lived lineage of hadrosaurs persisted nearly to the end of Cretaceous time in West Texas. ?G. alsatei was a contemporary of Edmontosaurus, the sole terminal Cretaceous hadrosaur in the northern Great Plains region, and neither possessed the ornate narial crest that characterized many earlier hadrosaurs.